(untitled) (Eurasian Scientific Herald, 2022)
The article deals with the problem of introducing inclusive education in the Republic of Uzbekistan, presents the results of a study conducted within the framework of the fundamental project "Creating a system of high-quality, continuous inclusive education in the Republic of Uzbekistan". The purpose of the article is a theoretical and statistical analysis of the inclusion of children with disabilities in educational institutions and the identification of barriers to their successful inclusion